Studi Aliran Daya pada PT. PLN (Persero) UIWS2JB UP3 Jambi ULP Kotabaru Penyulang Palem dengan Menggunakan Software Electric Transient and Analysis Program (ETAP) - Yono, Hadi Febra; Thamrin, NJ.; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2024)
Planning in the use of components in a power system needs to be done correctly. The planning will affect the optimization of the system in distributing power. Suboptimal power distribution will have an impact on the continuity of the power being distributed. The analysis that will be carried out is a power flow analysis. This research was taken using data from ULP Kota Baru Penyulang Palem, the location of this research is located in the distribution system area of Jambi City, Jambi Province, with the connection center at Penyulang Palem which is located in Kota Baru District, Jambi City, Jambi Province. . KVA is used to measure the total power in an electrical system. Total power includes active power and reactive power, so KVA provides a more complete picture of the power requirements of an electrical system. In the KVA measurement, it is assumed that all loads connected on a single line are 85%, 90%, 95%. That the greater the assumed load of the transformer and the farther away from the source, the greater the voltage drop / the smaller the voltage The greater the resistance the smaller the voltage drop, if the smaller the resistance then the drop will be larger. The wider the cross-section, the smaller the strain drop. The highest measurement of all loads is 3918 kv at the base of the source located near the bus in JB1100 assuming all loads of 95%.